Lewis acid triggered N-alkylation of sulfoximines through nucleophilic ring-opening of donor-acceptor cyclopropanes: synthesis of gamma-sulfoximino malonic diesters - More, Satish G.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2022)
Scandium triflate (Sc(OTf)(3)) catalyzed, mild, and regioselective ring-opening reaction of donor-acceptor (D-A) cyclopropanes has been developed using sulfoximines for the synthesis of gamma-sulfoximino malonic diesters. This protocol allows the synthesis of different N-alkyl sulfoximines in good to excellent yields (up to 94%) with broad functional group tolerance. In this process, N-H and C-C bonds are cleaved to form new C-N and C-H bonds. The feasibility of this method is supported by a gram-scale reaction and synthetic elaboration of the obtained product.